Meteorological Observations at Schiaparelli Glacier Automatic Weather Station (AWSrock), Cordillera Darwin, Chile, 2015-2020 - Christoph Schneider; Lukas Langhamer; Stephanie S Weidemann; Franziska Temme (PANGAEA, 2023)
The data set contains meteorological measurements from an automatic weather station installed on rock next to the glacier front (92 m a.s.l.) of Schiaparelli Glacier, Cordillera Darwin, Chile. The station has been installed by the Humboldt University Berlin in September 2015. It measures 2m air temperature (T), relative humidity (RH), solar radiation (SWin), wind speed (WS), wind direction (Dir) and precipitation (RRR) in an hourly interval (averaged, precipitation is accumulated). The data provided here has been corrected for outliers, radiative heating of the temperature sensor and sensor freezing.